Retail market situation in the Czech Republic in comparison with Russia. Differences, innovative approaches - Petrenko, Dmitrii (2021)
The research was conducted in order to describe and compare the current situation and digitalization trends in the Czech Republic and Russia. The author ran into the outlook of interconnection of digitalization with Russian and Czech retailing market by examining TOP- 5 retailing giants of both countries in order to reveal the full picture in current retailing and predict future opportunities. Concerning the methods used in the research, there was preferred to use both, qualitative and quantitative methods in order to remove limitations. For the qualitative data source, there was used already existing literature review, books and financial publications which cannot result in precise outcomes without the use of quantitative data source which compared and analyzed TOP-5 retailers from financial perspective including the volume of sales, growth rate, real GDP, average basket, and other indicators. As a result, it was revealed that Auchan from the Russian retailing sector and Ahold Group from Czech retailing sector were chosen as powerful and digitalized top players by hitting over 32.1 EUR bill and 74.7 EUR bill, relatively. In addition, in terms of annual growth rate of retailing turnover, Czech retailing sector resulted in being developed and digitalized that the one of Russia which scored 4.9% and 2.6%, relatively.